1985
DOI: 10.1080/09553008514551171
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Carcinogenesis in Experimental Animals and Its Implications for Radiation Protection

Abstract: Cancer induction is generally considered to be the most important somatic effect of low doses of ionizing radiation. It is therefore of great concern to assess the quantitative cancer risk of exposure to radiations of different quality and to obtain information on the dose-response relationships for carcinogenesis. Tissues in the human with a high sensitivity for cancer induction include the bone marrow, the lung, the thyroid and the breast in women. If the revised dosimetry estimates for the Japanese survivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The same group estimated RBE for both fibroadenoma and adenocarcinomas to be about 10, but in combination with diethylstilbestrol, RBE for adenocarcinomas and all mammary tumours rose to about 100 (Shellabarger et al, 1982). Broerse et al (1985Broerse et al ( , 1991 reported an RBE of 7 for 0.5 MeV neutrons vs x rays in a study of mammary fibroadenomas in a different colony of Sprague-Dawley rats than that used by Shellabarger et al (1980), and an RBE of 15 for adenocarcinomas in WAG/Rij rats.…”
Section: Ratsmentioning
confidence: 93%
“…The same group estimated RBE for both fibroadenoma and adenocarcinomas to be about 10, but in combination with diethylstilbestrol, RBE for adenocarcinomas and all mammary tumours rose to about 100 (Shellabarger et al, 1982). Broerse et al (1985Broerse et al ( , 1991 reported an RBE of 7 for 0.5 MeV neutrons vs x rays in a study of mammary fibroadenomas in a different colony of Sprague-Dawley rats than that used by Shellabarger et al (1980), and an RBE of 15 for adenocarcinomas in WAG/Rij rats.…”
Section: Ratsmentioning
confidence: 93%
“…The effects of UV radiation in nonhuman primates is not well known, although UV light in combination with other carcinogens applied to the skin of rhesus macaques has been linked to the development of skin tumors, including basal cell tumors (Palotay et al, 1976). Studies have been conducted using nonhuman primates to determine the effects of whole body irradiation, as well as the effects of therapeutic measures such as bone marrow transplantation (Broerse et al, 1985). In a study of the effects of simulated space irradiations, 1000 rhesus monkeys were exposed to various types of whole body irradiation using protons, electrons, neutrons, and X-rays (Splitter et al, 1973).…”
Section: Radiation Carcinogenesismentioning
confidence: 98%
“…A benefit of chemical radioprotection would be the inhibition of radiation carcinogenesis. Models for experimental tumor induction by ionizing radiation are not entirely satisfactory because of their long duration, while often only a moderate rate of tumor development is achieved (Broerse et al, 1985;Coggle, 1988;Covelli et al, 1988;Fry, 1981;Mole, 1984;Twentyman et al, 1980;Ullrich, 1983). Little work has been directed towards the question of how radioproteetive agents influence radiation carcinogenesis in vivo.…”
mentioning
confidence: 99%